An overview of Majlis Hari Kualiti dan Hari Keluarga in Yayasan Pembangunan Keluarga Darul Ta’zim 2016 / Noor Effarina Elias - Elias, Noor Effarina (2016)
This chapter consists of eleven sections. Section 1.2 is the background of Yayasan Pembangunan Keluarga Darul Ta’zim (YPKDT). Section 1.3 is Vision of YPKDT. Next, on Section 1.4 is the Mission of YPKDT. Section 1.5 is about the motto of YPKDT. Section 1.6 is about the objectives and Section 1.7 is the strategy. In addition, Section 1.8 is for the organization structure. The rational of YPKDT logo is in Section 1.9. Last but not least is Section 1.10, the chapter summary. Lastly in Section 1.11 is the chapter summary.